Life: The Natural History of an Early Christian Universe. Catherine Michael Chin - Sṭrumzah, Gedalyahu Gʹ. (The journal of theological studies, 2025)
This is an unusual book on the world of the Church Fathers, often intriguing, at times moving. The author’s poetic writing is enhanced by a number of image